Effects of ball properties on throwing in young team-handball beginners - Fasold, F.; Noël, B.; Nicklas, A.; Lukac, F.; Klatt, S. (International Journal of Sports Science & Coaching, 2022)
Throwing a ball is a primary skill in team-handball and can be directly influenced by the properties of different types of balls. Therefore, the use of different balls (i.e., methodic ball) recommended by the handball federations (e.g., IHF) and the education guidelines, are important in teaching throwing. Previous studies have shown that movement patterns and throwing velocity can be influenced by different ball types and sizes. However, the influence of these factors on throwing accuracy has not been investigated in detail yet. This study aims to replicate the findings of previous studies on increasing throwing velocity in children by comparing the use of a soft methodic ball with a size 0 handball. Furthermore, this study investigates the influence of these balls on throwing accuracy. In an experimental study, participants (10-years of age) threw a soft methodic ball and a size 0 ball at target areas in a handball goal. For all the throws, throwing velocity and accuracy were measured. Commensurate with previous research, throwing velocity was higher for the soft methodic ball compared to a size 0 ball. No difference was found in accuracy, although, it is worth mentioning that the participants were only experienced in throwing using the size 0 ball. Moreover, only one-third of the children favored throwing with a size 0 ball, which is what they are used to in training and competition. The results of our study, therefore, confirm that using soft methodic balls additionally, positively influences the throwing velocity and has no negative effect on the accuracy in throwing among young handball beginners.